Penerapan Konsep Project Based Learning Untuk Meningkatkan Kreativitas Siswa Kelas V Sekolah Dasar Negeri 192/1 Kampung Baru - Satria Fauzi Aldi Alfarezi; Vioni Saputri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The writing of this thesis is motivated by the low creativity found in students, educators have not used a variety of learning models in learning Natural and Social Sciences. The purpose of this research is to increase the creativity of students in Natural and Social Sciences subjects using the project-based learning model for classV. This research is a class action research of two cycles, each cycle consists of two meetings. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The subjects of this research were Class V students of State Elementary School 192/1 Kampung Baru. This research was conducted in the second semester of the 2024/2025 school year. At State Elementary School 192/1 Kampung Baru. The results of the research data analysis show that using the project-based learning model can increase student learning motivation in Natural and Social Sciences subjects in class V of State Elementary School 192/1 Kampung Baru. Details of the results of observations of students using the project-based learning model have increased from cycle I to cycle II with an average value of 66.66% in the less creative category and increased to 93.33% in the Creative category. It is concluded that using the Project-based Learning Model can increase student creativity in Natural and Social Sciences subjects in class V of State Elementary School 192/1 Kampung Baru.